Enabling management information systems and the quality of performance of public servants - Beatriz da Silva Pereira; Ilse Maria Beuren; Vanderlei dos Santos (Revista Contabilidade & Finanças)
ABSTRACT This article examines the influence of enabling Management Information Systems (MIS) on the quality of performance of public servants, mediated by commitment to the role. In light of social exchange theory, the study demonstrates that the use of enabling MIS positively influences the quality of performance of public servants and that commitment to the role mediates this relationship. A multigroup analysis reveals that public servants with different types of employment (permanent or commissioned) and varying length of service exhibit distinct effects in this relationship. The results present theoretical and practical implications by providing evidence that behavioral factors, such as commitment to the role, help explain the effect of enabling MIS on the quality of performance, and that personal aspects, such as employment type and length of service, impact the quality of performance in distinct ways. These findings are relevant for institutional policies and the quality of service delivered to citizens. The research offers new evidence, focusing on the public sector, regarding the role of enabling MIS in enhancing the quality of performance of public servants, with the mediating effect of commitment to the role. A survey was conducted with 252 employees of an institution responsible for upholding the state's legal order, and data analysis was performed using partial least squares structural equation modeling (PLS-SEM).